Neuropeptides as mediators of the early-life impact on the brain; implications for alcohol use disorders - Nylander, Ingrid; Roman, Erika (Frontiers in Molecular Neuroscience, 2012)
The brain is constantly exposed to external and internal input and to function in an ever-changing environment we are dependent on processes that enable the brain to adapt to new stimuli. Exposure to postnatal environmental stimuli can interfere with vital adaption processes and cause long-term changes in physiological function and behaviour. Early-life alterations in brain function may result in impaired ability to adapt to new situations, in altered sensitivity to challenges later in life and thereby mediate risk or protection for psychopathology such as alcohol use disorders (AUD). In clinical research the studies of mechanisms, mediators and causal relation between early environmental factors and vulnerability to AUD are restricted and attempts are made to find valid animal models for studies of the early-life influence on the brain. This review focuses on rodent models and the effects of adverse and naturalistic conditions on peptide networks within the brain and pituitary gland. Importantly, the consequences of alcohol addiction are not discussed but rather neurobiological alterations that can cause risk consumption and vulnerability to addiction. The article reviews earlier results and includes new data with emphasis on endogenous opioid peptides but also oxytocin and vasopressin. These peptides are vital for developmental processes and it is hypothesized that early-life changes in peptide networks may interfere with neuronal processes and thereby contribute the individual vulnerability for AUD. The summarized results indicate a link between early-life rearing conditions, opioids and ethanol consumption and that the ethanol-induced effects and the treatment with opioid antagonists later in life are dependent on early-life experiences. Endogenous opioids are therefore of interest to further study in the early-life impact on individual differences in vulnerability to AUD and treatment outcome.